TGF-β, IL-1β, IL-6 levels and TGF-β/Smad pathway reactivity regulate the link between allergic diseases, cancer risk, and metabolic dysregulations - Elkoshi, Zeev (Frontiers in Immunology, 2024)
The risk of cancer is higher in patients with asthma compared to those with allergic rhinitis for many types of cancer, except for certain cancers where a contrasting pattern is observed. This study offers a potential explanation for these observations, proposing that the premalignant levels of circulating transforming growth factor-β (TGF-β), IL-1β, and IL-6 as well as the reactivity of the TGF-β/Smad signaling pathway at the specific cancer site, are crucial factors contributing to the observed disparities. Circulating TGF-β, IL- β and IL-6 levels also help clarify why asthma is positively associated with obesity, Type 2 diabetes, hypertension, and insulin resistance, whereas allergic rhinitis is negatively linked to these conditions. Furthermore, TGF-β/Smad pathway reactivity explains the dual impact of obesity, increasing the risk of certain types of cancer while offering protection against other types of cancer. It is suggested that the association of asthma with cancer and metabolic dysregulations is primarily linked to the subtype of neutrophilic asthma. A binary classification of TGF-β activity as either high (in the presence of IL-1β and IL-6) or low (in the presence or absence of IL-1β and IL-6) is proposed to differentiate between allergy patients prone to cancer and metabolic dysregulations and those less prone. Glycolysis and oxidative phosphorylation, the two major metabolic pathways utilized by cells for energy exploitation, potentially underlie this dichotomous classification by reprogramming metabolic pathways in immune cells.